PENGARUH EXPERIENTIAL MARKETING & EMOTIONAL BRANDING TERHADAP REPURCHASE MELALUI BRAND TRUST (Studi Kasus pada Konsumen Garuda Indonesia di Kota Semarang) - Bonaventura Ega Wicaksono; Agung Budiatmo (Universitas Diponegoro, 2018)
A brand competition requires a company to have a good marketing strategy and an appropriate branding decision that can encourage consumers to repurchase. Experiential marketing and emotional branding are some of the factors that can influence the level of brand trust perception to improve consumer repurchase. Therefore, the company must be able to maximize the strategy of experiential marketing and emotional branding to achieve high level of brand trust perception so that repurchase consumer to service is high. This type of research is explanatory research, with data collection techniques through questionnaires and interviews. Sampling technique using purposive sampling. The sample in this study amounted to 100 respondents in Semarang City. The method used to analyze the primary data in this research is using validity test, reliability test, correlation coefficient, simple and multiple regression analysis, determination coefficient, one way test of significance (t test), and 2-stage regression with SPSS 16.0.The results showed that the partial and simultaneous influence between experiential marketing, emotional branding, and brand trust against repurchase. Based on result of regression analysis 2 stage show that brand trust is variable between to variable repurchase. Based on the results of the research, the researcher suggested that Garuda Indonesia to optimize the experiential marketing and emotional branding strategy by continuously making innovations in terms of service both pre-flight, in-flight and post flight as well as in terms of technology enjoyed by consumers. In addition, the need for consistency in maintaining the quality of services provided in accordance with the needs of consumers so that brand trust will be higher in the minds of consumers and affect the level of repurchase services.